Correction of a Mucogingival Defect Using an Implant-Retained Postoperative Stent in a Severely Resorbed Mandible: Case Report - Nascimento de Melo, Luiz Gustavo; Ciporkin, Frederico; Maia Neto, Jose Sergio; Fraga de Almeida, Ana Lucia Pompeia; Scarelli Lopes, Jose Fernando; Marcio Figueiredo, Caio; Nagata, Maria José Hitomi [UNESP] (Quintessence Publishing Co Inc, 2008)
This case report describes a technique that uses a palatal mucosal graft and an acrylic resin postoperative stent in an attempt to increase the layer of keratinized tissue around osseointegrated implants in an atrophic mandible. During second-stage surgery a split-thickness labial flap is reflected and apically repositioned by being sutured onto the periosteum and connective tissue. A palatal mucosal graft is then sutured onto the recipient site. The stent is worn for at least 4 weeks following surgery. This procedure helps to eliminate mobility of the mucosa in the area, deepen the vestibule, and prevent muscle reinsertion. (Int J Periodontics Restorative Dent 2008;28:617-623.)